Carbon Dot-Modulated Phase-Change Composites for Wide Temperature Range and High-Density Heat Storage and Release - Jingya Liang; Ning Li; Jie Wu; Qing Chang; Jinlong Yang; Shengliang Hu (Energies)
Organic phase-change materials (PCMs) offer great promise in addressing challenges in thermal energy storage and heat management, but their applications are greatly limited by low energy density and a rigid phase transition temperature. Herein, by introducing carbon dots (CDs) with abundant oxygen-related groups, we develop a novel kind of erythritol (ET)-based composite PCMs (CD-ETs) featuring an enhanced latent heat storage capacity and a reduced degree of supercooling compared to pure ETs. The optimally formulated CD-ETs increase the latent heat storage capacity from 377.3 to 410.2 J·g−1 and the heat release capacity from 209.0 to 240.2 J·g−1 compared to the pristine ETs. Moreover, the subcooled degree of CD-ETs is more than 30 °C lower than that of pristine ETs. By successively encapsulating CD-ETs and CD-containing polyethylene glycol (PEG) with a low melting point in a reduced graphene oxide-modified melamine sponge, the resultant shape-stabilized system not only prevents leakage of molten PCMs but also allows for a wide response temperature window and promotes the heat transfer ability of melted PEG in close contact with solid CD-ETs. Stepped melting and crystallization guarantee phase changes in high-melting-point ETs via solar heating, Joule heating or a combination thereof. Specifically, the melting enthalpy of this system is as high as 306.5 J·g−1, and its cold crystallization enthalpy reaches 196.5 J·g−1, surpassing numerous organic PCMs. This work provides a facile and efficient strategy for the design of ideal thermal energy storage materials to meet the needs of application scenarios in a cost-effective manner.